2022
DOI: 10.3390/audiolres12040045
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Recurrent Benign Paroxysmal Positional Vertigo: The Role of Combined Supplementation with Vitamin D and Antioxidants

Abstract: Benign paroxysmal positional vertigo (BPPV) usually has a favorable course, although it is possible to observe BPPV with a high recurrence rate. Previous studies suggested that vitamin D deficiency might affect BPPV recurrences, and oxidative stress might play a complementary role in BPPV pathogenesis. This multicentric trial aimed to evaluate the effectiveness of oral nutritional supplementation with a compound of alpha-lipoic acid, Carnosine, and Zinc (LICA® (Difass International, Coriano (RN), Italy)), vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…We conducted a review of the study results on vitamin D supplementation for preventing recurrences of BPPV within the last 3 years ( Table 2 ). Out of the five articles examined, the majority, four out of five, reported that vitamin D supplementation in BPPV patients effectively prevented recurrence of BPPV [ 19 , 20 , 21 , 29 ]. Consistently, these studies showed that the group supplemented with vitamin D exhibited a lower recurrence rate compared to the control group without vitamin D supplementation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted a review of the study results on vitamin D supplementation for preventing recurrences of BPPV within the last 3 years ( Table 2 ). Out of the five articles examined, the majority, four out of five, reported that vitamin D supplementation in BPPV patients effectively prevented recurrence of BPPV [ 19 , 20 , 21 , 29 ]. Consistently, these studies showed that the group supplemented with vitamin D exhibited a lower recurrence rate compared to the control group without vitamin D supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…Libonati et al conducted a study reporting that oral nutritional supplementation with vitamin D3 plus antioxidants could prevent relapses in patients suffering from high-recurrence BPPV, assessing the BPPV recurrence rate based on patients experiencing two or more episodes of BPPV within the previous 6 months or at least three episodes in the previous 12 months [ 21 ]. A total of 128 patients with high-recurrence BPPV involving the posterior semicircular canal or the lateral semicircular canal (both in geotropic and apogeotropic forms) were randomized into three arms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding vitamin D deficiency, a previous meta-analysis demonstrated that it was an independent risk factor for BPPV occurrence and recurrence 38 ; this correlation may be explained by the fact that vitamin D deficiency may disrupt calcium metabolism in the inner lymphatic fluid and bone metabolism, leading to osteoporosis and increasing the risk of BPPV 39 . A recent multicentric study suggested that oral nutritional supplementation with vitamin D3 may prevent relapses in patients suffering from a high number of recurrent episodes of BPPV 40 . Further large-scale studies are necessary to establish the role of vitamin D supplementation in prevention of BPPV recurrence.…”
Section: Discussionmentioning
confidence: 99%